Huntington’s disease modeling on HEK293 cell line - D. V. Sharipova; T. B. Malankhanova; A. A. Malakhova (Вавиловский журнал генетики и селекции)
Huntington’s disease is a hereditary neurodegenerative disorder caused by CAG trinucleotide repeat expansion in the first exon of HTT gene. The mutant HTT protein has an elongated polyglutamine tract and forms aggregates in the nuclei and cytoplasm of the striatal neurons. The pathological processes occurring in the medium spiny neurons of Huntington’s disease patients lead to neurodegeneration and consequently to the death. The molecular mechanisms of the pathology development are difficult to study due to the limited material availability and late onset of the manifestation. Therefore, one of the important tasks is generation of an in vitro model system of Huntington’s disease based on human cell cultures. The new genome editing approaches, such as CRISPR/Cas9, allow us to generate isogenic cell lines that can be useful for drug screening and studying mechanisms of molecular and cellular events triggered by certain mutation on an equal genetic background. Here, we investigated the viability and proliferative rate of several mutant HEK293 cell clones with mutations in the first exon of HTT gene. The mutant clones were obtained earlier using CRISPR/Cas9 genome editing technology. We showed that mutant cells partially reproduce the pathological phenotype, that is, they have reduced proliferation activity, an increased level of apoptosis and high sensitivity to treatment with 5μM MG132 proteasome inhibitor compared to the original HEK293 Phoenix cell line. Our results indicate that the mutation in the first exon of HTT gene affects not only neurons, but also other types of cells, and HEK293 cell clones bearing the mutation can serve as in vitro model for studying some mechanisms of HTT functioning.